Гнездование курганника на Украине - Стригунов, В.И. (Вестник зоологии, 1982)
Two inhabited nests of Buteo rufinus (Cretzschm) were found. and two nestlings were captured in the Kirovograd Region (Ukraine) in 1980-1981. The data from literatureand author's finding support a nidea of existence in the Ukraine of an isolated population of long-legged buzzard.